Molecular Detection of Genetic Material of Toxoplasma gondii in Goat Blood Samples from Northern Thailand - Koonyosying, Pongpisid; Muenthaisong, Anucha; Sangkakam, Kanokwan; Nontasaya, Kanpitcha; Rittipornlertrak, Amarin; Nambooppha, Boondarika; Apinda, Nisachon; Maneekesorn, Supawadee; Sthitmatee, Nattawooti (Veterinary sciences, 2025)
Toxoplasmosis is a significant parasitic zoonosis caused by Toxoplasma gondii. Among livestock animals, small ruminants, especially sheep and goats, are the most infected. This infection is a leading cause of abortion, resulting in considerable economic losses for goat breeders. The present study aimed to assess the prevalence of T. gondii infection in goats in northern Thailand, with an emphasis on its potential zoonotic transmission to humans. Polymerase chain reaction (PCR) targeting the T. gondii dihydrofolate reductase-thymidylate synthase (Tgdhfr-ts) gene was employed for molecular detection. This represents the first report of T. gondii molecular detection in blood samples from small ruminants in Thailand by PCR. A total of 176 meat goat blood samples were analyzed, yielding an 8.52% (15/176) positivity rate for T. gondii DNA. The selected DNA sequences from the positive T. gondii DNA displayed a high degree of nucleotide sequence homology with the reference Tgdhfr-ts sequence. Phylogenetic analysis revealed a single clade alongside other T. gondii strains, showing no differentiation based on genotype. This study contributes to the understanding of T. gondii epidemiology and provides a foundation for future strategies to control and manage T. gondii transmission in livestock populations.